Carbon formation on the surface during the reduction of iron oxide particles by CO and CO/H2 mixtures. (21st September 2019) - Lu, Feng; Wen, Liangying; Chen, Yangxin; Zhong, Hong; Xu, Jian; Zhang, Shengfu; Yang, Zhongqing
Graphical abstract: Highlights: The promising routes of carbon formation by CO and CO/H2 mixtures was investigated by DFT. An innovation kinetic model was used to predict the rate of carbon formation. The reasons was given to explain the effects of hydrogen addition on the formation of carbon shell. Abstract: Carbon deposition on the iron surface is of great interest due to a good performance to prevent sticking during the direct reduction (DR) in the fluidized bed. The promising routes of carbon formation were investigated by the density function theory (DFT). An innovative kinetic model, which considers adsorption and decomposition of CO, is applied to control the carbon content of direct reduction iron in the two-stages reduction process. The results show that the CO bond of CO is stretched due to the attractive force of surface iron atoms on the C and O atoms. The added H2 can significantly improve this CO bond stretch to decrease the barrier energy of CO decomposition. The formation of carbon is sensitive to the temperature and the added H2 can extend the temperature range for carbon formation and reduce the temperature of the maximum rate of carbon formation. Besides, the proper concentration of H2 added in the CO/H2 mixtures can improve the formation of carbon shell. However, the carbon shell will not be formed under a condition of extremely high mole fraction of H2 because H2 increases the adsorption energy of CO on the iron surface.